Efek Mediasi Kepuasan Pelanggan atas Pengaruh Kualitas Produk dan Store Atmosphere terhadap Loyalitas Pelanggan - Tjandra Gunawan; Fathorrahman Fathorrahman; Yunus Handoko (University of Merdeka Malang, 2019)
The purposes of this study are : 1) to determine the direct effect of product quality and store atmosphere on customer loyalty, 2) to determine the indirect effect of product quality and store atmosphere on customer loyalty through customer satisfaction as an intervening variable. This research is a field research with quantitative methods. The data collection uses a field survey method using a research instrument in the form of a questionnaire with a 5-points scale of likert. Population of this research are Vosco Coffee's customers. Samples taken are 150 customers selected by accidental-purposive sampling technique.. The results of path analysis reveal that: 1) directly, both product quality and store atmosphere have a positive and significant effect on customer loyalty; 2) customer satisfaction is also proven to be able to mediate the influence of product quality and store atmosphere on customer loyalty even though this indirect influence is not as big as direct influence. https://doi.org/10.26905/jmdk.v7i2.3347